Influenza virus RNA replication in vitro: synthesis of viral template RNAs and virion RNAs in the absence of an added primer. - Shapiro, G I (1988)
The two steps in influenza virus RNA replication are (i) the synthesis of template RNAs, i.e., full-length copies of the virion RNAs, and (ii) the copying of these template RNAs into new virion RNAs. We prepared nuclear extracts from infected HeLa cells that catalyzed both template RNA and virion RNA synthesis in vitro in the absence of an added primer. Antibody depletion experiments implicated nucleocapsid protein molecules not associated with nucleocapsids in template RNA synthesis for antitermination at the polyadenylation site used during viral mRNA synthesis. Experiments with the WSN influenza virus temperature-sensitive mutant ts56 containing a defect in the nucleocapsid protein proved that the nucleocapsid protein was indeed required for template RNA synthesis both in vivo and in vitro. Nuclear extracts prepared from mutant virus-infected cells synthesized template RNA at the permissive temperature but not at the nonpermissive temperature, whereas the synthesis of mRNA-size transcripts was not decreased at the nonpermissive temperature. Antibody depletion experiments showed that nucleocapsid protein molecules not associated with nucleocapsids were also required for the copying of template RNA into virion RNA. In contrast to the situation with the synthesis of transcripts complementary to virion RNA, no discrete termination product(s) were made during virion RNA synthesis in vitro in the absence of nucleocapsid protein molecules.